2014
DOI: 10.1002/mds.26117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D from different sources is inversely associated with Parkinson disease

Abstract: Background An inverse association between Parkinson disease (PD) and total vitamin D levels has been reported but it is unknown whether vitamin D from different sources, i.e. 25(OH)D2 (from diet and supplements) and 25(OH)D3 (mainly from sunlight exposure), all contribute to the association. Methods Plasma total 25(OH)D, 25(OH)D2, and 25(OH)D3 levels were measured by liquid chromatography-tandem mass spectrometry in PD patients (N=478) and controls (N=431). Total 25(OH)D was categorized by clinical insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 39 publications
2
58
0
3
Order By: Relevance
“…Several epidemiological studies have evaluated the potential association between serum vitamin D concentrations and PD. Four US‐based case‐control studies have reported a higher prevalence of vitamin D deficiency in PD patients than in controls or a dose‐response relationship between serum 25(OH)D concentrations and the odds of PD . One study conducted in the Faroese population did not find any association .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several epidemiological studies have evaluated the potential association between serum vitamin D concentrations and PD. Four US‐based case‐control studies have reported a higher prevalence of vitamin D deficiency in PD patients than in controls or a dose‐response relationship between serum 25(OH)D concentrations and the odds of PD . One study conducted in the Faroese population did not find any association .…”
Section: Discussionmentioning
confidence: 96%
“…For instance, studies have demonstrated that administration of 1,25‐dihydroxyvitamin D 3 attenuates the toxic effects of 6‐hydroxydopamine on nigrostriatal dopaminergic neurons in rats . Multiple epidemiological studies have shown that relative to controls, PD cases have lower serum/plasma levels of 25‐hydroxyvitamin D (25(OH)D), a measure of vitamin D sufficiency status . However, interpretation of these cross‐sectional comparisons is not straightforward because of concerns about reverse causation because sun exposure influences 25(OH)D levels and PD patients may be less likely to spend time outdoors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the first epidemiological risk study from Finland found lower baseline vitamin D levels in individuals who went on to develop PD compared to those who did not, but the more recent prospective Atherosclerosis Risk in Communities (ARIC) study cohort of almost 13,000 subjects found no association between baseline vitamin D levels and risk of PD 17 years later . Moreover, whereas studies involving populations with more advanced PD have consistently shown associations between decreased vitamin D and PD, they face potential confounding attributed to reduced sun exposure, leading to reduced dermal synthesis of Vitamin D, in patients with progressive motor limitations.…”
mentioning
confidence: 99%
“…Although the evidence for this is weak, early studies suggest that PD mortality is higher in the northern regions of the United States . The point has been made that age‐adjusted PD incidence is slightly higher in Finland when compared with California, Minnesota, and New York City . It is also higher in the Faroe Islands between Norway and Iceland .…”
mentioning
confidence: 99%